Emergency medical service interventions and experiences during pandemics: A scoping review. - Despina Laparidou; Ffion Curtis; Nimali Wijegoonewardene; Joseph Akanuwe; Dedunu Dias Weligamage; Prasanna Dinesh Koggalage; Aloysius Niroshan Siriwardena (PLoS ONE)
Background The global impact of COVID-19 has been profound, with efforts to manage and contain the virus placing increased pressure on healthcare systems and Emergency Medical Services (EMS) in particular. There has been no previous review of studies investigating EMS interventions or experiences during pandemics. The aim of this scoping review was to identify and present published quantitative and qualitative evidence of EMS pandemic interventions, and how this translates into practice. Methods Six electronic databases were searched from inception to July 2022, supplemented with internet searches and forward and backward citation tracking from included studies and review articles. A narrative synthesis of all eligible quantitative studies was performed and structured around the aims, key findings, as well as intervention type and content, where appropriate. Data from the qualitative studies were also synthesised narratively and presented thematically, according to their main aims and key findings. Results The search strategy identified a total of 22,599 citations and after removing duplicates and excluding citations based on title and abstract, and full text screening, 90 studies were included. The quantitative narrative synthesis included seven overarching themes, describing EMS pandemic preparedness plans and interventions implemented in response to pandemics. The qualitative data synthesis included five themes, detailing the EMS workers' experiences of providing care during pandemics, their needs and their suggestions for best practices moving forward. Conclusions Despite concerns for their own and their families' safety and the many challenges they are faced with, especially their knowledge, training, lack of appropriate Personal Protective Equipment (PPE) and constant protocol changes, EMS personnel were willing and prepared to report for duty during pandemics. Participants also made recommendations for future outbreak response, which should be taken into consideration in order for EMS to cope with the current pandemic and to better prepare to respond to any future ones. Trial registration The review protocol was registered with the Open Science Framework (osf.io/2pcy7).